New record of Grateloupia taiwanensis S.-M. Lin et H.-Y. Liang in Vietnam: Evidence of morphological observation and rbcL sequence analysis - XUAN-VY XUAN-NGUYEN; TRUNG-HIEU NGUYEN; VIET-HA DAO; LAWRENCE LIAO (Society for Indonesian Biodiversity, 2019)
Abstract. Nguyen XV, Nguyen TH, Dao VH, Liao L. 2019. New record of Grateloupia taiwanensis S.-M. Lin et H.-Y. Liang in Vietnam: Evidence of morphological observation and rbcL sequence analysis. Biodiversitas 20: 688-695. Members of Grateloupia show highly diverse morphological traits, and this makes species classification more difficult.  Samples were found growing with other marine algae nearshore, 3–5 m depth at Da Nang City. Morphological observation of vegetative and reproductive structures as well as phylogenetic analysis based on the large subunit of ribulose-1,5-bisphosphate-carboxylase-oxygenase (rbcL) sequence confirmed its identification.  Phylogeny of members of Grateloupia inferred from Bayesian Inference, Maximum Likelihood, Maximum Parsimony and Neighbour Joining indicated materials collected in Vietnam compared well with known G. taiwanensis from the type locality, with very little sequence divergence. Grateloupia taiwanensis S.-M. Lin et H.-Y. Liang is therefore reported for the first time from Vietnam.